Junior Doctors as senior clinical leaders – a reflection on my foundation year 2 (F2) experiences during the SARS-CoV-2 COVID-19 pandemic. (2nd January 2021) - Home, Joseph
ABSTRACT: COVID-19 presented a huge unplanned pressure on health resources worldwide. Across the NHS, different approaches have been utilized to respond to the crisis. Leadership figures across services were faced with difficult decisions with potential scarcity of resources never before seen by NHS providers. In the medium-sized District General Hospital where I am based, one of the key changes implemented, was the placement of a Junior Doctor into Hospital management and Leadership teams. Under direct supervision from the Medical Director and Associate Director of Medical Education, I was released from a significant proportion of my clinical work to provide leadership and oversight into decisions affecting junior doctors. As a Foundation Doctor in my final rotation of Foundation Year 2, this provided a unique experience to not only observe senior policy and strategic decision making, but also to lead on several projects. Coming from a Trust with historically poor performance metrics in trainee experience, it was recognized that this was an opportunity to instigate both structural and cultural change across divisions. This article will discuss the lessons learned from this experience, highlighting areas for improvement, with the hope of empowering junior doctors to take senior leadership roles in the future.